ELECTRONIC GOVERNANCE AND SERVICE DELIVERY IN INDIA: THEORY AND PRACTICE - S. N. Sangita Bikash Chandra Dash (INSTITUTE FOR SOCIAL AND ECONOMIC CHANGE, 2005)
Interest in e-governance is growing with the increasing use of information and communication technology (ICT) by government to improve the quality of governance and service delivery. Governments all over the world have been using ICTs such as internet, websites, computers and mobile phones to provide various government services in an efficient, equitable and transparent manner with less corruption (good governance). Notwithstanding these advantages, there are certain problems like poor coverage of the e-governance infrastructure, inadequate human resources, mismanagement, technical inexperience and inequitable access (digital divide), lack of public awareness and ineffective civil society participation. This paper mainly reviews the experiences of e- governance reforms in improving the quality of governance and service delivery in India. The first section deals with the conceptual framework of e-governance. The second section focuses on egovernance initiatives in India. The third section reviews the implications of egovernance on service delivery in terms of efficiency, accountability, participation and equity on the basis of the secondary resources. The fourth section deals with the enabling conditions in promoting e-governance in India. Finally, the paper comes with the policy perspectives.